Have labour market reforms at the turn of the millennium changed job durations of the new entrants? A comparative study for Germany and Italy - Gianna Claudia Giannelli; Ursula Jaenichen; Claudia Villosio (Institute for the Study of Labor (IZA), 2009)
According to the aims of the labour market reforms of the 90s implemented in many European countries, workers may stay at their first job for a shorter time, but should be able to switch jobs easily. This would generate a trade-off between job opportunities and job stability. This paper addresses this issue using administrative longitudinal data for Germany and Italy, taken as representative examples of continuous and isolated reforms, respectively. The estimated piecewise constant job and employment duration models show that changes in the durations of the first job and employment - measured as the sum of multiple consecutive jobs - are observed in periods of labour market reforms. However, the existence of a trade-off is not confirmed by the results. In Germany, men have experienced an increase in employment stability over time, mated with somewhat longer job durations, while women have not benefitted from an increase in employment durations as a compensation for the marked decrease in their first job durations. In Italy, employment stability of the new entrants of both sexes has not improved after the reforms. The reduction in the duration of the first job has not been counterbalanced by an increase in the opportunity to find rapidly another job. These results suggest that the objective of increasing job opportunities by means of labour market deregulation has not been fully achieved.
Keywords: J62; J64; J68; K31; C41; 330; Employment duration; work career; tenure; precarious jobs; labour market reforms; mixed proportional hazard; Arbeitsmarktpolitik; Reform; Arbeitsmarktflexibilisierung; Wirkungsanalyse; Arbeitsmobilität; Betriebszugehörigkeit; Arbeitsplatzsicherung; Ungeschützte Beschäftigung; Erwerbsverlauf; Deutschland; Italien